2013
DOI: 10.23986/afsci.7887
|View full text |Cite
|
Sign up to set email alerts
|

Biochar can restrict N2O emissions and the risk of nitrogen leaching from an agricultural soil during the freeze-thaw period

Abstract: Freeze-thaw (FT) events in soils can cause a burst of nitrous oxide (N 2 O) and enhance N leaching during the springthaw event. We studied whether a soil amended with wood-derived (spruce chips) biochar (10 tonnes ha -1 ), produced at rather low temperatures (400-450°C), could reduce the burst of N 2 O and the risk of N leaching from an agricultural soil after a FT event. A short-term laboratory experiment (4 weeks) was conducted with 24 vegetated (Phleum pratense) mesocosms (12 controls, 12 biochar-treated) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The application of biochar reduces soil CO 2 emissions due to a negative priming effect (Zimmerman et al 2011;Chintala et al 2014;Cross and Sohi 2011;Major et al 2010a;Steinbeiss et al 2009;Sagrilo et al 2015) and N 2 O emissions are reduced significantly through various mechanisms (Jia et al 2012;Renner 2007;Cayuela et al 2014). These mechanisms include that (1) the proportion of N 2 O transformation to N 2 during denitrification is changed due to the change of pH (Sun et al 2014); (2) the abundance of soil microbes is changed (Zhu et al 2017), in particular, the increase in the growth and activity of microorganisms involved in denitrification (Bruun et al 2011); (3) the adsorption ability of soil to NH 4 + or NO 3 − is improved (Kettunen and Saarnio 2013;Van Zwieten et al 2010;Case et al 2012); (4) soil aeration is enhanced and the denitrification rate is reduced (Rogovska et al 2011;Augustenborg et al 2011). In general, biochar demonstrates a significant effect on soil N cycle, although the effects are not exactly the same across various studies due to the differences in soil characteristics, management practices, and application methods Wang et al 2012;Quin et al 2014).…”
Section: Carbon Sequestration and Emission Reductionmentioning
confidence: 99%
“…The application of biochar reduces soil CO 2 emissions due to a negative priming effect (Zimmerman et al 2011;Chintala et al 2014;Cross and Sohi 2011;Major et al 2010a;Steinbeiss et al 2009;Sagrilo et al 2015) and N 2 O emissions are reduced significantly through various mechanisms (Jia et al 2012;Renner 2007;Cayuela et al 2014). These mechanisms include that (1) the proportion of N 2 O transformation to N 2 during denitrification is changed due to the change of pH (Sun et al 2014); (2) the abundance of soil microbes is changed (Zhu et al 2017), in particular, the increase in the growth and activity of microorganisms involved in denitrification (Bruun et al 2011); (3) the adsorption ability of soil to NH 4 + or NO 3 − is improved (Kettunen and Saarnio 2013;Van Zwieten et al 2010;Case et al 2012); (4) soil aeration is enhanced and the denitrification rate is reduced (Rogovska et al 2011;Augustenborg et al 2011). In general, biochar demonstrates a significant effect on soil N cycle, although the effects are not exactly the same across various studies due to the differences in soil characteristics, management practices, and application methods Wang et al 2012;Quin et al 2014).…”
Section: Carbon Sequestration and Emission Reductionmentioning
confidence: 99%
“…Some studies further demonstrated that freeze-thaw induced GHGs emissions were important parts of the annual GHGs budget (Liang et al 2007, Wolf et al 2010. In a short-term laboratory study, Kettunen and Saarnio (2013) found that soils amended with biochar decreased soil N 2 O emissions by 61% during freeze-thaw cycles (FTC). However, to the best of our knowledge, there have been no studies on responses of soil CO 2 and CH 4 emissions to biochar addition during FTC.…”
mentioning
confidence: 99%
“…However, freeze-thaw cycles led to significantly higher although small amounts of CO 2 emissions from biochar amended soil compared to the control soil, indicating some small effects of freeze-thaw events on biochar degradation. This can possibly be explained by the disruption of small biochar-soil aggregates, generating particles susceptible to microbial attack (Eastman, 2011), In another experiment, biochar significantly reduced both ammonium and nitrate leaching and N 2 O emissions from vegetated soil cores subjected to freeze-thaw events, assumedly due to N-retention (Kettunen and Saarnio, 2013). The same tendency was observed in data from a grassland field experiment, indicating that this interaction requires further attention (Schimmelpfennig et al, 2014).…”
Section: Disturbance Eventsmentioning
confidence: 82%